2007
DOI: 10.1016/j.pain.2007.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Oral and spinal melatonin reduces tactile allodynia in rats via activation of MT2 and opioid receptors

Abstract: The antiallodynic effect of melatonin after intrathecal (it) and oral administration as well as the possible participation of MT(2) and opioid receptors in melatonin-induced antiallodynia in neuropathic rats were assessed. Ligation of the L5/L6 spinal nerves produced a clear-cut tactile allodynia in the rats. Intrathecal (3-100 microg) and oral (37.5-300 mg/kg) administration of melatonin decreased tactile allodynia induced by spinal nerve ligation. Intrathecal administration of the preferential MT(2) receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 43 publications
3
60
0
Order By: Relevance
“…This hypothesis is supported by the relation between BDNF and pro-inflammatory cytokines that has been demonstrated in FM patients [62-64]. Melatonin has marked anti-inflammatory effects on peripheral sites by inhibiting the release of pro-inflammatory cytokines [12]. Additional mechanisms involved in melatonin’s effect on pain pathways include an important reduction of nitric oxide (NO) and malondialdehyde (MDA) levels, two compounds that are closely related to inflammation [65].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This hypothesis is supported by the relation between BDNF and pro-inflammatory cytokines that has been demonstrated in FM patients [62-64]. Melatonin has marked anti-inflammatory effects on peripheral sites by inhibiting the release of pro-inflammatory cytokines [12]. Additional mechanisms involved in melatonin’s effect on pain pathways include an important reduction of nitric oxide (NO) and malondialdehyde (MDA) levels, two compounds that are closely related to inflammation [65].…”
Section: Discussionmentioning
confidence: 94%
“…Noradrenergic projections from the locus coeruleus produce similar effects [25]. Together, this evidence justifies assessing the effect of melatonin in the descending modulatory pain systems, alone or combined with classic therapeutic agents such as amitriptyline, as it has been demonstrated that melatonin increases the pain threshold in healthy subjects [26], improves sleep quality [15] and modulates systems involved in pain, such as the GABAergic and opioidergic systems [12,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the effect of MLT was also blocked by the subcutaneous and intrathecal administration of naltrexone, thus indicating that opioids are also likely involved in the analgesic properties of MLT. 164 Arreola-Espino and colleagues 162 found that the oral administration of MLT dose-dependently reduced flinching behaviour in the 0.5% formalin test and tactile allodynia in diabetic rats. Remarkably, the MT 2 receptor antagonist K-185 blocked the effects due to MLT treatment.…”
Section: Mt 2 Receptors and Painmentioning
confidence: 97%
“…160 Studies aimed at assessing the role of MLT receptors in the analgesic effect of MLT have shown that MT 2 and not MT 1 receptors are likely involved. [161][162][163][164] Yoon and colleagues 161 found that an intrathecal injection of MLT dose-dependently attenuated the flinching response during phases 1 and 2 of the formalin test in rats. The analgesic effect of MLT was blocked by the intrathecal administration of luzindole or 4P-PDOT, and consequently, it was mediated by the MT 2 receptor.…”
Section: Mt 2 Receptors and Painmentioning
confidence: 99%
See 1 more Smart Citation